Observation of D0 Meson Decays to π+π−μ+μ− and K+K−μ+μ−Final States; Physical Review Letters; Vol. 119, iss. 18 - Aaij R. Roel; Adeva B. Bernardo; Adinolfi M.; Ajaltouni Z. J. Zeina; Akar S. Simon; Vagner A. R. Aleksandr Rudolfovich (2017, 2017)
Title screen